Fiscal decentralization, local government innovation preference, and enterprise technological innovation: Evidence from China - Jie Tu (PLoS ONE, 2026)
Fiscal decentralization influences the allocation of attention and effort by local governments across multiple tasks, consequently impacting enterprise technological innovation within their jurisdictions. This represents a significant institutional constraint on corporate innovation. Employing a sample of A-share listed companies that regularly published annual financial reports from 2015 to 2023, this study constructs a moderated mediation model within a three-tier “central government – local government – enterprise” principal-agent framework. It is the first to uncover the intrinsic mechanism and property-right heterogeneity through which fiscal decentralization affects the technological innovation of microeconomic entities. The empirical findings reveal: (1) Overall, fiscal decentralization exerts a significant inhibitory effect on enterprise technological innovation, providing micro-level empirical support for the “decentralization inhibition theory”. (2) Local government preference for innovation serves as a mediator between fiscal decentralization and enterprise technological innovation. Fiscal decentralization indirectly influences enterprise innovation by shaping local governments’ innovation priorities. (3) The mediating effect of local government innovation preference exhibits property-right dependence. Fiscal expenditures on science and technology and innovation incentive policies by local governments trigger arbitrage behavior in private enterprises, creating a “crowding-out effect” on their technological innovation. As “special market entities,” state-owned enterprises (SOEs) combine the advantages of both market and governmental economic coordination mechanisms. Fiscal decentralization, by influencing local government innovation preference, effectively promotes technological innovation in SOEs. These empirical results offer policy implications for accelerating the formation of new institutional frameworks compatible with new quality productive forces, particularly concerning central-local relations, government-enterprise relations, and the functional positioning of SOEs.